It's all the rage! Exploring the nuances in the link between vaping and adolescent delinquency. (July 2019) - Jackson, Dylan B.; Boccio, Cashen M.; Leal, Wanda E.; Vaughn, Michael G.
Abstract: Purpose: The present study examines the relationship between vaping different substances (i.e., flavor, nicotine, and marijuana) and adolescent delinquency while accounting for traditional forms of nicotine and marijuana use. Methods: We employ a sample of 8th and 10th grade youth from the 2017 cohort of the Monitoring the Future (MTF) study - a nationally representative, ongoing study of substance use and related risk factors. Results: Findings suggest a link between vaping and delinquency that, under certain circumstances, surpasses the association between illicit substance use through traditional means and delinquency. Of all of the vaping and substance-using groups identified, results indicate that youth who ingest marijuana through a vape exhibit the highest risk of delinquent involvement and are at significantly greater risk of delinquent behavior than youth who vape non-illicit substances (e.g., flavor) and those who ingest illicit substances through traditional means. Conclusions: The findings suggest that there may be something criminogenic about vaping among adolescents, but that the strength of the relationship between vaping and delinquency is contingent on what is being vaped, with marijuana vaping being most heavily correlated with delinquency. Policies and programmatic initiatives are needed to try to curb this dangerous new drug trend. Highlights: The relevance of adolescent vaping trends for criminological inquiry has been largely overlooked. We examine whether vaping different substances is linked to adolescent delinquency. A large, national sample of youth in 8th and 10th grade during the year 2017 is employed. In some cases, vaping is linked to a higher risk of delinquency than traditional substance use. Policies and programmatic initiatives are needed to try to curb this dangerous new drug trend.